Effect of Incorporating Super Bond Additives on Volumetric and Mechanical Characteristics of Cold Mix Asphalt Concrete using Asbuton - Rosman Hidayatulloh; I Dewa Made Alit Karyawan; Ervina Ahyudanari (JURNAL TEKNIK UNILAK, 2021)
Asbuton is the natural asphalt of Buton Island, Southeast Sulawesi. Asbuton has substantial reserves with deposits estimated at between 150 to 300 million tons. Asphalt mixture using Asbuton can be done with a cold mix. This mixture requires a rejuvenating agent that serves to soften and rejuvenate the asphalt properties contained in Asbuton. The rejuvenation process that is less than optimal results in the low quality of the asphalt mixture. Therefore, it is necessary to conduct a study to improve the performance of cold mixtures using Asbuton. In this study, super bond additives were used. This study aims to determine the extent to which the performance of asphalt-concrete mixtures using Asbuton with the addition of super bond additives in the rejuvenating agent is increased. The addition of additives was varied with levels of 0.0%, 0.2%, 0.3%, and 0.4%, so that the impact could be known. The best asphalt concrete mix characteristics were obtained at the addition of 0.4% additives. Where, for volumetric characteristics the values ​​obtained are: Void in the Mix (VIM) 5.08%, Void in Mineral Aggregate (VMA) 19.6% and Void Filled with Bitumen (VFB) 74.0%. While the mechanical characteristics are: Stability 609 kg, Flow 2.7 mm and Marshall Quotient 223 kg/mm. Only the Marshall Quotient value does not meet the minimum requirements, because it is < 250 kg/mm.